Integrated optical devices using bacteriorhodopsin as active nonlinear optical material - Dér, A.; Fábián, L.; Valkai, S.; Wolff, E.; Ramsden, Jeremy J.; Ormos, P. (Cranfield University, 2006)
Coupling of optical data-processing devices with microelectronics, telecocommunication and sensory functions, is among the biggest challenges in molecular electronics. Intensive research is going on to find suitable nonlinear optical materials that could meet the demanding requirements of optoelectronic applications, especially regarding high sensitivity and stability. In addition to inorganic and organic crystals, biological molecules have also been considered for use in integrated optics, among which the bacterial chromoprotein, bacteriorhodopsin (bR) generated the most interest. bR undergoes enormous absorption and concomitant refractive index changes upon initiation of a cyclic series of photoreactions by a burst of actinic light. This effect can be exploited to create highly versatile all-optical logical elements. We demonstrate the potential of this approach by investigating the static and dynamic response of several basic elements of integrated optical devices. Our results show that, due to its relatively high refractive index changes, bR can be used as an active nonlinear optical material to produce a variety of integrated optical switching and modulation effects.